Assessment of degenerative changes in the atlanto-odontoid joint using cone-beam computed tomography (CBCT) imaging - Peker, Ramazan Berkay; Sezgin, Omer Said; Kayipmaz, Saadettin; Dönmez, Senem Tuğra (PeerJ, 2025)
Background This study sought to evaluate the severity of osteoarthritis in the atlanto-odontoid joint (AOJ) using cone-beam computed tomography (CBCT) and analyse its distribution by age and sex. Materials and Methods The CBCT images of 215 patients (130 females, 85 males; aged 18–80 years) taken for dental purposes were retrospectively analysed. The severity of the osteoarthritis in the AOJ was graded from 0 to 3, while its relationships with age and sex were assessed via ordinal and binary logistic regression analyses. Results Osteoarthritis-related changes were detected in 64.7% of patients (62.3% of females, 68.3% of males). Females showed 44.3% decreased odds of severe osteoarthritis compared to males (p = 0.041). Individuals aged 18–29 showed 99.9% decreased odds of severe osteoarthritis, those aged 30–39 showed 99.7% decreased odds, those aged 40–49 showed 99.4% decreased odds, those aged 50–59 showed 97.1% decreased odds, and those aged 60–69 showed 96.0% decreased odds of severe osteoarthritis compared to individuals aged 70–80 (all p < 0.01). Each additional year of age increased the risk of osteoarthritis by 8.0% (OR: 1.080; p < 0.001) (odds ratio (OR): 1.080; p < 0.001), although it was not significantly associated with sex (p = 0.248). Conclusion CBCT is effective in detecting degenerative changes in the AOJ. Moreover, it is associated with lower radiation doses than conventional CT. Ageing significantly increases both the probability and the severity of osteoarthritis. Routine AOJ evaluation during CBCT imaging may significantly enhance clinical decision-making by enabling the early detection and management of osteoarthritis.
Keywords: Radiology; Atlanto-odontoid joint; Cone-beam computed tomography; Odontoid process; Osteoarthritis; Cervical vertebrae